2005
DOI: 10.1111/j.1749-7345.2005.tb00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of a Small-Scale Recirculating System for Ongrowing of Captive Wild Black Sea Bass Centropristis striata in North Carolina

Abstract: An economic analysis of a hypothetical small‐scale marine recirculating aquaculture system (RAS) is conducted for ongrowing small, wild black sea bass Centropristis striata at the University of North Carolina Wilmington, Center for Marine Science (UNCW‐CMS) aquaculture facility in Wrightsville Beach, North Carolina (NC). The analysis is based on production data from field trials and marketing data from the sale of tank‐grown product. The growout facility consists of four 16.7‐m3 (dia. x ht. = 5.58 × 1 m) fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…So sensitivity analysis denoted that farm business viability is very sensitive to sale price changes received for harvested product, highlighting the largest impact on annual returns (Copeland et al, 2005;Penney and Mills, 2000) with respect to other parameters (De Ionno et al, 2006;Hart et al, 2013). Moreover, simulations confirmed that offshore production system performed a better economic profitability also by varying current prices of output and some inputs, especially thanks to a better feed conversion ratio and to a higher fish density (Kim et al, 2012).…”
Section: Sensitivity Analysismentioning
confidence: 89%
“…So sensitivity analysis denoted that farm business viability is very sensitive to sale price changes received for harvested product, highlighting the largest impact on annual returns (Copeland et al, 2005;Penney and Mills, 2000) with respect to other parameters (De Ionno et al, 2006;Hart et al, 2013). Moreover, simulations confirmed that offshore production system performed a better economic profitability also by varying current prices of output and some inputs, especially thanks to a better feed conversion ratio and to a higher fish density (Kim et al, 2012).…”
Section: Sensitivity Analysismentioning
confidence: 89%
“…This variation has been chosen taking into account the volatility of prices and productive factors that could happen in the market as function of the current economic conditions, as well as in other studies [88,89].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…This range of variation was chosen taking into account the volatility of prices and production factors foreseeable in the market as a function of the current economic conditions, in accordance with other studies Copeland et al, 2005).…”
Section: Sensitivity Analysismentioning
confidence: 99%